Advantage of Collaboration Workflows in the Automotive Supply Chain: Case Study on the Automotive Cluster of Slovenia - Oman, Simon (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Strengthening of collaboration among individual business partners has proved essential for the structuring of Slovenian economy and enhancing competitive advantage on the global market. At the same time, ontology, as an important concept of business collaboration among individual business partners, has been proposed for the collaboration of information systems in the supply chain. The present paper presents a case study of internet-based collaboration workflows in the automotive supply chain. Furthermore, the paper reveals a prototype solution, describing a concept of integration between the Enterprise Resource Planning (ERP) and open source business process management software. The partners in the Automotive Cluster of Slovenia (ACS), striving to make use of internet services in their operations, are consequently allowed to integrate into the supply chain. The result ensures that the competitiveness of small and medium-sized enterprises (SMEs) does not depend on internal IT infrastructure although their IT collaboration is supported by open source collaborative workflows.